2016
DOI: 10.1177/0021998316636206
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and test of flexural performance of polyvinyl alcohol-steel hybrid fiber reinforced cementitious composite

Abstract: The flexural performance of polyvinyl alcohol-steel hybrid fiber reinforced engineered cementitious composite with characteristics of low drying shrinkage special focus on impacts of steel fiber content and matrix strength has been investigated in both experimental and theoretical aspects in this paper. Four matrix types with water to binder ratio of 0.25, 0.35, 0.45, and 0.55 and three additional steel fiber contents in the composite with polyvinyl alcohol fiber content of 1.7% in volume were used in the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…With the development of structural engineering, high‐strength concrete (HSC) or ultra‐high‐strength concrete (UHSC) characterized by a lower water‐to‐binder ratio, addition of fine and active admixtures (i.e., silica fume, fly ash and ground granulated blast furnace slag, and so on) as well as special curing technologies is proposed and designed by a large number of researchers and engineers . However, it has been widely recognized that concrete, especially HSC or UHSC, is a typical brittle material, and after its first cracking in tension, localization of deformation will occur immediately followed by decreasing load . Resultantly, the durability and life of concrete structures are deteriorated seriously.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…With the development of structural engineering, high‐strength concrete (HSC) or ultra‐high‐strength concrete (UHSC) characterized by a lower water‐to‐binder ratio, addition of fine and active admixtures (i.e., silica fume, fly ash and ground granulated blast furnace slag, and so on) as well as special curing technologies is proposed and designed by a large number of researchers and engineers . However, it has been widely recognized that concrete, especially HSC or UHSC, is a typical brittle material, and after its first cracking in tension, localization of deformation will occur immediately followed by decreasing load . Resultantly, the durability and life of concrete structures are deteriorated seriously.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, a class of high‐performance fiber‐reinforced cementitious composite, called engineered cementitious composite (ECC), has been micromechanically developed to provide an ultimate strength higher than the first cracking strength . The typically extreme tensile strain capacity of ECC can be more than 2% while only a moderate amount of fibers (generally less than 2% in fraction) is required .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the distance was smaller, the thickness of the weak link of the fiber-matrix layer was thinner which indicated that the fiber could adhere the matrix with much fastness; this meant that the mechanical strength was well developed. As assumed, the CaCO 3 whiskers were well dispersed in the three-dimensional direction in the cement paste and the equation of the average distance of the CaCO 3 whiskers was shown as follows [24][25][26]:…”
Section: Micromechanical Mechanismsmentioning
confidence: 99%